Exploring justification in solving mathematics problems in a facebook group - Imam Rofiki; Alfi Syahrin Siregar (Pusat Studi Pengembangan Pembelajaran Matematika, 2025)
Facebook is a popular platform that supports the development of critical thinking skills through its discussion feature. One of these potentials is its use to encourage mathematical discussions and explore justification skills in solving problems. Mathematical justification skills include providing logical reasons for the steps in solving problems. This study aims to explore the mathematical justification of Facebook users in answering questions uploaded in Facebook groups. The justification levels refer to Back, Mannila, and Wallin: assumption, vague/broad statement, rule, procedural description, and own explanation. This study used a qualitative approach with an explorative research design. The study participants were 222 members of the SMP (Solution of Mathematics Problem) Facebook forum. Data were obtained through documentation of uploaded questions, comments from forum members, and non-participatory online observation. This study analyzed answers to three geometry problems uploaded in the forum, with six people selected as research subjects based on the diversity of their justification patterns. The results showed variations in the level of mathematical justification of forum members, from assumption to own explanation. Factors influencing differences in justification levels include understanding mathematical concepts and critical thinking skills. These findings indicate that Facebook can effectively encourage mathematical discussions and improve critical thinking skills.